Management of Property of Minors Under Guardianship - Syelvia Margretha; Benny Djaja (PT Publikasiku Academic Solution, 2023)
Management of guardianship of minors is the provision of services in the case of minors under the power of guardians which includes supervision of the performance of guardian duties over minors who are not under the control of parents and management of the child's property or property as regulated by law. A person can also be determined to be the guardian of a child through the determination/decision of the District Court or Religious Court. Generally, child guardianship applications for Islamic religion are submitted to the Religious Court, and for non-Muslim religions guardianship applications are submitted to the District Court. In practice, however, applications for guardianship of children to be Muslim can be filed with the District Court. Provisions regarding the appointment of a child's guardian through the court can be seen in Articles 359 to Article 364 of the Civil Code. In addition, Article 107 paragraph (3) also stipulates